Possible Means and Methods of Logotherapy in Supervision (Training and Practice : Journal of Educational Sciences, 2015)
In this study I intend to introduce to what extent the theoretical background of logotherapy is compatible with the theory, the principle and the actual practice of professional personality development (supervision) and how the rhetoric of logotherapy can be applied in the cases of professional development. I will address the issue whether Frankl’s image of man is in harmony with the aims of supervision. I will give an account of the logotherapic tools and methods, which according to my views, can be beneficial to the development of professional personality. While touching upon the tools and methodological repertoire of logotherapy, I will also introduce the ways of dereflection, paradoxical intention and attitude modulation. I will speak about the dialogue form and the rhetoric of logotherapy and its application in supervision. I will also mention mind sensibility training, Socratic dialogue, guided curriculum vitae and the special stage.